2003
DOI: 10.1179/000349803225001436
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalences of cystic echinococcosis, and the associated risk factors, in rural–agricultural, bedouin and semi-bedouin communities in Jordan

Abstract: An ELISA was used to determine the seroprevalence of cystic echinococcosis (CE), caused by Echinococcus granulosus, in representatives of the rural-agricultural, semi-bedouin and bedouin communities of Jordan. The knowledge, attitudes and practices (KAP) pertaining to the transmission of CE in such communities were also investigated. In the ELISA, serum samples from 2388 subjects were tested for IgG antibodies reacting with antigens in crude sheep hydatid fluid (CSHF). The rural-agricultural subjects were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
7
20
4
Order By: Relevance
“…The United Kingdom, the Middle East, and North Africa have reported higher numbers of affected women [1,25,26]. However, this is in contrast to studies conducted by Cohen et al and Qaqish et al, wherein such associations were not observed [27,28].…”
Section: Discussioncontrasting
confidence: 64%
“…The United Kingdom, the Middle East, and North Africa have reported higher numbers of affected women [1,25,26]. However, this is in contrast to studies conducted by Cohen et al and Qaqish et al, wherein such associations were not observed [27,28].…”
Section: Discussioncontrasting
confidence: 64%
“…Field studies for CE in potentially endemic regions can provide valuable baseline prevalence data and can be used for surveillance of the human population as part of control programs. Serology is the method generally used for prevalence surveys in developing countries (Schenone et al 1999;Qaqish et al 2003;Pastore et al 2003). Tests that detect the antigen-antibody reaction known as the arc 5 were used for surveillance of human populations in endemic regions of Peru (Coltorti and VarelaDiaz 1978;Mercado et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Hydatidosis induced by Echinococcus granulosus remains an important parasitic disease mainly in the Mediterranean region (Lahmar et al, 1999) and in south America (Qaqish et al, 2003;Raether and Hanel, 2003;Romig, 2003;Seimenis, 2003) both in human and in veterinary medicine. The economic impact is important in terms of livestock losses (Torgerson, 2003;Umur and Kaaden, 2003).…”
Section: Introductionmentioning
confidence: 99%